Intergenerational transmission of domestic violence in refugee families in Durban, South Africa - Maksudi, Kassa (Department of Social Development, 2025)
The World Health Organization in 2021 reported that 30% of women globally experience violence, with South Africa being infamous for particularly high rates of violence against women, including domestic violence. Despite this, domestic violence experiences and its intergenerational transmission among refugee women living in South Africa remain underexplored. Refugee women living in South Africa are a vulnerable and marginalised population with regard to domestic violence, as their refugee status and other risk factors disproportionately increase their vulnerability. This qualitative embedded single case study adopted an integrated conceptual framework that includes concepts from Heise's ecological framework, social learning theory, and attachment theory to explain the theory of intergenerational transmission. The study aimed to investigate how domestic violence is transmitted intergenerationally among refugee women from Burundi and the Democratic Republic of Congo living in Durban, South Africa. A total of 30 mother-adult daughter pairs of refugee women from Burundi and the Democratic Republic of Congo were purposively sampled through focus group discussions and individual semi-structured interviews. Data was analysed using thematic and case study analysis. The findings revealed a complex interplay of psychosocial mechanisms, including internalisation, socialisation, silencing, re-enactment, guilt, and the influence of the family of origin, all embedded within multi-level risk factors. Some of these risk factors include exposure to domestic violence, lack of social support, refugee status, attitudinal acceptance, and gender norms, contributing to the transmission of domestic violence both within the first generation and from the first to the second generation. Findings also revealed potential protective factors that may be used in culmination with risk factors and psychosocial mechanisms of transmission, which could be critical for informing targeted responses to domestic violence within the study group, underscoring a critical need for targeted interventions. By elucidating specific factors and mechanisms influencing the intergenerational transmission of domestic violence among refugee families, this study enhances our understanding of how domestic violence can be interrupted across generations. It also guides research interventions and policy recommendations. This study also underscores the importance of religious, culturally sensitive, and context-specific approaches in addressing and preventing domestic violence and its transmission across generations in refugee populations.